Interrelation of Islamic Formal and Islamic Principles in The Context of The Country’s Constitution (The Application of Islamic Law for Corruptors in Indonesia) - Imam Syafi’i; Subairi (Cyber Media Indonesia, 2020)
Corruption has made the life of the state have porous joints. Economy as the mainstay of the joint life experience fragility, currency values decline significantly. Social joints also suffer the same fate, now corruption has become commonplace in everyday life portrait began to level the structure of RT (Neighborhood) up to the level of institution of the President. In fact, even this body of organisms may have been